Advancement in the Development of Models for Hepatitis C Research. (30th May 2012) - Carcamo, Wendy C.; Nguyen, Cuong Q.
Abstract : Hepatitis C virus (HCV) is a pandemic disease affecting an estimated 180 million individuals worldwide and infecting each year another 3-4 million people making HCV a global public health issue. HCV is the main cause for chronic hepatitis, cirrhosis, and hepatocellular carcinoma. In the United States, HCV-related chronic liver disease is a leading cause of liver transplantation. Despite significant improvements in antiviral drugs, only 50% of treated patients with HCV have viral clearance after treatment. Showing unique species specificity, HCV has a narrow range of potential hosts infecting only chimpanzees and humans. For decades, the chimpanzee model has been the only and instrumental primate for studying HCV infection; however, availability, economic, and ethical issues make the chimpanzee an unsuitable animal model today. Thus, significant research has been devoted to explore different models that are suitable in studying the biology of the virus and application in the clinical research for developing efficient and tolerable treatments for patients. This review focuses on experimental models that have been developed to date and their findings related to HCV.